Eph-ephrin signaling affects lens growth and shape, nucleus size, and gradient refractive index in adult mice - Flowers, Gryffin M.; Wang, Kehao; Hoshino, Masato; Uesugi, Kentaro; Yagi, Naoto; Pierscionek, Barbara; Cheng, Catherine (Frontiers in Ophthalmology, 2025)
PurposeThe function of the eye lens, to fine focus light from different distances onto the retina to form a clear image, relies on tissue biomechanical properties, refractive index, shape, and transparency. Increased lens stiffness with age, especially of the center or nucleus, has long been hypothesized to lead to presbyopia, a loss of accommodative ability, and the need for reading glasses. The cellular and molecular mechanisms that determine lens biomechanical properties and change during age-related stiffening remain unclear. Little is known about the factors that regulate lens shape and growth, nucleus size, and refractive index. We previously showed that loss of EphA2, a receptor tyrosine kinase, or ephrin-A5, a ligand for Eph receptors, leads to changes in lens shape and resilience in 2-month-old mice. Surprisingly, the loss of EphA2 led to smaller and softer lens nuclei with no change in lens stiffness.MethodsUsing coverslip compression and X-ray phase tomography, we investigated whether lens stiffness, resilience, morphometric changes, and gradient refractive index (GRIN) were altered in lenses from 4- and 8-month-old adult mice with disruption of Eph-ephrin signaling. ResultsOur data revealed no obvious changes in lens stiffness or resilience between control and ephrin-A5 knockout (KO or -/-) mice at 4 and 8 months of age. While there were no differences in lens resilience, EphA2-/- lenses were stiffer than control lenses from 8-month-old mice. At all ages, EphA2 and ephrin-A5 KO lenses were more spherical in shape, and EphA2-/- lens nuclei were smaller than controls. In 4- and 8-month-old mice, EphA2-/- lenses were small. Measurement of GRIN in control and KO lenses revealed that EphA2-/- lenses had decreased magnitudes of refractive index across the GRIN profile in all age groups. ConclusionsThese results suggest that, at least in mouse lenses, the size of the lens and nucleus does not affect whole tissue stiffness with age. Our work indicates that Eph-ephrin signaling influences lens shape and normal adult whole lens growth while EphA2 is needed for nuclear size and appropriate GRIN.